THE COGNITIVE LINGUISTIC INTERPRETATION OF TOPONYMS AND THEIR ROLE IN THE LINGUISTIC WORLDVIEW (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Toponyms represent more than arbitrary referential labels; they encapsulate cognitive processes of spatial conceptualization, environmental perception, and cultural encoding. Grounded in cognitive linguistics and the German tradition of the "linguistic worldview" (sprachliches Weltbild), this expanded article analyzes German place names as reflections of embodied cognition, image schemas, metonymy, and metaphor. Motivational patterns—descriptive (topographical and hydrological), possessive/settlement-based, functional, and substrate influences—are examined in depth, with regional variations highlighting historical migrations and worldview shifts. An extended table provides categorized examples, frequencies, and cognitive interpretations. Findings demonstrate how toponyms contribute to mental mapping, collective identity, and linguistic relativity, fossilizing perceptual salience and human-landscape interactions in the German sprachliches Weltbild. Implications for cognitive onomastics, cultural linguistics, and interdisciplinary studies are discussed.